National Council of Juvenile and Family Court Judges: NCJFCJ (NCJFCJ)
The National Council of Juvenile and Family Court Judges ist the oldest judicial membership organization in the country and provides all judges, courts and related agencies involved with juvenile, family and domestic violence cases with the knowledge and skills to improve the lives of the families and children who seek justice